Cabin dynamics simulation of “Rope Metro” transport system - I. A. Lagerev; A. V. Lagerev; A. V. Panfilov; E. V. Marchenko (Advanced Engineering Research, 2018)
Introduction. The study results of the passenger ropeways (PRW) applicability in the highly urbanized environment are presented. Issues on the development of mathematical models for designing and simulating work processes of the advanced “Rope Metro” transport system are considered. The proposed transport system differs significantly from the customary PRW. For its successful design, a mathematical model for estimating the operational loading of the key components is developed. Likewise, a mathematical submodel of the passenger cabin of the cable car which will be then integrated into the composite mathematical model of the system is offered by the authors. The work objective is to study the passenger cabin oscillations during its movement along the section of the transport system.Materials and Methods. A new mathematical model describing the oscillations of the passenger cabin and its suspension members is proposed. This model should be integrated into the composite mathematical model of the transport system using part of its output capacity. Numerical simulation of the cabin movement is carried out. The derived equations represent a mathematical model for studying the dynamics of the pendular oscillations of the passenger cabin of the advanced “Rope Metro” transport system. In the paper, the integration of the equations is carried out by the Runge-Kutta method in the program package of the in-home design.Research Results. New mathematical models and software for the numerical simulation are developed. The damping devices’ effect on the maximum oscillation amplitude of the passenger cabin is shown.Discussion and Conclusions. The results obtained can be used under designing and modeling work processes, and optimizing the transport system components. It is proved that the damping device reduces the amplitude of the oscillations which stabilize at lower values (0.3-0.5 degrees) after the transient process end. In the future, it is required to integrate the developed mathematical model into a composite model of the system under investigation to refine the conclusions reached.